Faith-Based Environmental Stewardship as Informal Education: Lessons from Rural Muslim Communities in Lombok, Indonesia - M. Saipul Watoni; Abdul Haris Rasyidi (Lembaga Bale Literasi, 2025)
Purpose: This study explores how faith-based environmental stewardship practices in rural Muslim communities in Lombok, Indonesia, function as an embedded system of informal environmental education. Despite growing scholarly interest in community-based and indigenous approaches to environmental learning, the pedagogical dimensions of Islamic ecological practices in non-Western rural settings remain underexplored. Methodology: Drawing on an ethnographic approach, this study employed participant observation, in-depth semi-structured interviews, and documentary analysis across three rural villages in Lombok over an eight-month period. Thematic analysis guided the interpretation of data from thirty-two community members, including religious leaders, farmers, youth, and women. Results: Four interlocking themes emerged: (1) the mosque and Islamic religious gatherings as ecological classrooms; (2) ritualized environmental practices as lived curriculum; (3) intergenerational transmission of faith-based ecological knowledge through community elders and religious figures; and (4) Islamic faith as an intrinsic motivational framework for pro-environmental agency that transcends fear-based or economic incentive approaches. Conclusions: The findings suggest that faith-based environmental stewardship constitutes a sophisticated, culturally embedded pedagogical system capable of sustaining ecological values across generations. These practices challenge the dominance of formal, school-centred models in environmental education research and offer transferable lessons for place-based, community-anchored environmental education policy and practice globally.